Abu Nasr al Farabi and understanding of the collective person’s inner world in psychology (The Journal of Psychology and Sociology, 2017)
The article shows the influence of al-Farabiteachings about the subject as a microcosm of the collective personpsychology, understanding of his inner world and representation mechanisms of the others person'slive.How the semantic analysis of the inner world is conducted in the process of overcoming the difficulties of life: (1) meditative intimate dialogue with persons associated with the overcoming of tunnel vision; (2) the selection of positive values and meanings introduced by our intimate life of individuals, working with imagery and visualization; (3) we analyze what methods were used to overcome our intimate personality in the process of overcoming difficulties and relate with their resources. At this stage it is very important to differentiate the technologies of psychological defense and coping behavior. Techniques of psychological protection work in the initial time. Lingering their use threatens a problem of acute stress related to the future with an awareness of the problem; (4) it is the process of integrating the possible ways to overcome, on the basis of awareness and understanding of their own resources and circumstances, as a result of the set of associations.
Keywords: subject; inner peace; intimate personality; representation; subject reflected; semantic analysis; psychological defense; coping.